If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12a + 8b = 0 Solving 12a + 8b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8b' to each side of the equation. 12a + 8b + -8b = 0 + -8b Combine like terms: 8b + -8b = 0 12a + 0 = 0 + -8b 12a = 0 + -8b Remove the zero: 12a = -8b Divide each side by '12'. a = -0.6666666667b Simplifying a = -0.6666666667b
| 7/8(16) | | 8x-4=-10x-3 | | 6(x-9)=24 | | 12x+5y=24547 | | 36w^2+39w+75=-2w-4 | | 1-6r=4-3r | | n+6=-12 | | 4(3x-2)=22 | | 39+4y-1=14y-11-3y | | 6y+8=3y+8 | | Lots(1000)=3 | | 10y-9=4y+3 | | 7x+19-2x-7= | | 8y^2x= | | 25-6x=5-8x | | -7/8*16 | | X/5-6=-10 | | 13=6x-3-5x | | -7/8x16 | | E^x^1/6 | | 6(y+5)=9y+9 | | 5x-22=2-7x | | -6(6x-1)=-174 | | (2x^5)(-2x^8)(3x^6)= | | 2(z-1)=5(z+8)-15 | | (5u+4)(9-u)=0 | | -3(1x+2)=-21 | | 7x^2-40x=2x^2-5x | | 59=6x+x+10 | | (11x+3)+(6x-5)= | | 3*5xytu=5 | | 3xy=8x |